Analisis Paparan Penduduk terhadap Bahaya Longsor dan Jalur Evakuasi Bencana di Kecamatan Karangpandan, Kabupaten Karanganyar - Handini Riang Pramesti; Agus Anggoro Sigit; M. Iqbal Taufiqurrahman Sunariya; Choirul Amin (Mataram University, 2026)
Karangpandan District is one of the districts in Karanganyar Regency that experiences a high incidence of landslides, this is influenced by its location in the transition zone between the lowlands and the foothills of Mount Lawu, causing Karangpandan District to have a varied topography. This study aims to analyze the level of exposure of residents in Karangpandan District to landslide hazard zones according to Karanganyar Regent Regulation Number 83 of 2022 and determine landslide disaster evacuation routes in Karangpandan District as part of disaster mitigation. This study was conducted using a spatial approach, using scoring analysis for the level of population exposure and network analysis to determine evacuation routes with starting points from locations with a history of landslides to evacuation sites. Determination of evacuation sites is based on capacity, accessibility, level of population exposure, availability of toilets, and open spaces. The results show that the level of population exposure in Karangpandan District is dominated by the high class, with 16 evacuation routes with a travel time of <10 minutes. Therefore, routes that pass through areas with high levels of population exposure and have shorter travel times can be prioritized as the main evacuation route.